Psychological contract breach and mental health: the role of equity sensitivity and self-control - Wyk, B.V.; Hasford, F.; Nyakale, N.; Vangu, M. (Health and Technology, 2024)
Background Computer software for absorbed dose quantification has been widely used in nuclear medicine. Different software tools have been written to improve dose assessment, especially in therapeutic nuclear medicine. Some software tools focusing on computational phantom models from the international commission of radiation protection and units (ICRP) while others on Monte Carlo-simulated models. While many studies have investigated therapeutic nuclear medicine dosimetry,. The authors have noticed that very few papers compare therapeutic software tools to each other; hence, a doctor of philosophy study was embarked on. The aim of our study was therefore to validate our in-house-developed software tool, Masterdose, using the commercial software, OLINDA/EXM 1.0, that was available in our department. Methods: Methodology was based on clinical patient data treated for neuroendocrine tumours with 177Lutetium (Lu)-DOTATATE at a South African hospital. All patients underwent the same SPECT acquisition protocol and were corrected for scatter. partial volume, collimator-detector response, gamma camera calibration, and attenuation. Correction factors were applied to images to convert counts to activity. The first cycle of peptide receptor radionuclide therapy (PRRT) for 11 single photon emission computed tomography (SPECT) patients were compared using the Masterdose and OLINDA/EXM 1.0 software tools at 1, 24, 72, and 168 h. Cumulated activity and the absorbed dose were compared for the two software tools. The absorbed dose difference was then compared using statistical Bland-Altman analysis. Results Masterdose and OLINDA/EXM 1.0 had different peptide receptor radionuclide therapy methodologies. This led to different results obtained for the software tools. The cumulative activities of Masterdose and DTK was 10.5% and 10.9% for the kidneys and tumors, respectively. On average, tumor-absorbed doses were nine times those of the kidneys. Bland–Altman analysis shows a non-systematic difference between the two software. Conclusion On average, the relative percentage difference between the cumulated activities and absorbed dose of the two software were 10.7%.
Research Article
Keywords: Software; Dosimetry; Therapeutic